The Immunization Coverage of Afghan Children at the Health Centers Supported by the United Nation Higher Commission in Kerman, Iran - Azizallah Dehghan; Narges Khanjani; Rouhollah Zahmatkesh (Shahid Sadoughi University of Medical Sciences, 2013)
Introduction: Immunization is one of the most important health programs in first level prevention and is also one of the most cost-effective prevention programs in the entire world. This study evaluates the situation of immunization in fewer than one year old Afghan refugee children in Kerman, Iran. Materials and Methods: This was a cross-sectional study. Data was extracted from the records of the health centers supported by the higher commission of refuges in Kerman. The BCG, polio 0, DTP 3, polio 3, Hepatitis B 3 and MMR 1 was calculated and compared with the vaccine coverage in Iran and Afghanistan. Stata 11 and Excel 2007 and the chi-square statistics were used for the analysis. Results: The coverage of all BCG, Polio 0, DTP 3, Polio 3, Hepatitis B 3 and MMR 1 vaccines in the Afghan immigrants residing in Kerman between 2010 and 2012 was more than 95%. This coverage was not significantly different from the vaccine coverage of Iranian children, but was significantly higher than the vaccine coverage of children residing in Afghanistan. Conclusion: The vaccine coverage of Afghan children residing in Kerman is similar to Iranian children and is high and satisfactory. These results show part of The Islamic Republic of Iran's commitment for providing health requirements for Afghan refugees residing in Iran.